Surfing Tourists’ Preferences in Choosing Type of Accommodation in the Mentawai Islands - Rifan Andika; Muhammad Baiquni (Journal of Indonesian Tourism and Development Studies, 2021)
As a tourist destination, the Mentawai Islands have many potential tourism destinations such as marine tourism especially surfing spots. Many surfers come to the Mentawai Islands from all around the world. Most of the tourists are young adults with an average income of USD 20.000-40.000 annually. Most are intermediate to pro-level surfers. The biggest reason why so many surfers come to visit the Mentawai Islands is for the exceptional surfing experience, which comes from the quality of its natural environment as one of the top preferences. Based on location, there are two types of accommodation, city accommodation and resort accommodation. On the other hand, surfers' preference in choosing accommodation type needs to be discovered. There will be preferences, at least surfers have three, which are Price, Facility, and Location. Price compatibility with quality, availability of surfing transport, proximity to surf breaks becomes the main preferences in choosing accommodation.Keywords: Accommodation, Mentawai Islands, surf.